The Effect of Early Mobilization on the Uterine Involution Process in Postpartum Mothers at the Gandasuli Community Health Center - Sartika Paemboan; Widia Shofa Ilmiah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Early mobilization is an important component of postpartum care that may influence the speed of uterine involution. Delayed uterine involution can increase the risk of postpartum complications, including hemorrhage and prolonged recovery. This study aimed to analyze the relationship between early mobilization and uterine involution among postpartum mothers at Gandasuli Public Health Center. An analytical observational study with a cross-sectional design was conducted from September to November 2025. The study population consisted of 56 postpartum mothers, selected using a total sampling technique. The independent variable was early mobilization, categorized based on the type of activity performed, while the dependent variable was uterine involution assessed through uterine fundal height reduction. Data were analyzed using descriptive statistics and Kendall’s tau-b correlation test. The results showed that most respondents practiced early mobilization, particularly standing and walking, and the majority experienced rapid uterine involution. Bivariate analysis revealed a statistically significant relationship between early mobilization and uterine involution (τ = -0.321; p = 0.010). In conclusion, early mobilization is significantly associated with faster uterine involution among postpartum mothers. Promoting early mobilization should be emphasized as part of routine postpartum care to support maternal recovery.